Comparison of Levofloxacin Versus Clarithromycin Based Triple Therapy in the Eradication of H. Pylori Infection in Patients Visiting Tertiary Care Hospital in Peshawar (Journal of Medical & Health Sciences Review, 2025)
Background: Helicobacter pylori infection is a major cause of chronic gastritis, peptic ulcer disease, and gastric malignancy worldwide. The effectiveness of standard clarithromycin-based triple therapy has declined over recent years due to increasing antibiotic resistance, particularly in developing countries. Levofloxacin-based triple therapy has emerged as a potential alternative with improved eradication rates.Objective: To compare the efficacy, safety, and compliance of levofloxacin-based versus clarithromycin-based triple therapy in eradication of H. pylori infection among patients attending a tertiary care hospital in Peshawar.Methods: This comparative cross sectional study was conducted on 240 H. pylori-infected patients. Patients were divided into two equal groups receiving either levofloxacin-based or clarithromycin-based triple therapy for 14 days. Assessment of eradication was conducted 4-6 weeks after treatment was administered in terms of urea breath test or stool antigen test.Results: The eradication rate was much more in levofloxacin group (85.8%) than in clarithromycin group (71.7%) (p = 0.004). Side effects were mild in both groups and metallic taste disturbance was significantly more common in clarithromycin group. In both groups the compliance was high.Conclusion: Levofloxacin-based triple therapy provided higher eradication rates and comparable safety and compliance, showing it may be a more suitable first-line treatment option in regions with high clarithromycin resistance.